Assessing the need for evacuation assistance in the 100 year floodplain of South Florida. (February 2016) - Prasad, Shivangi
Abstract: The main objective of this study is to assess evacuation assistance need in the 100 year floodplain of South Florida (Palm Beach, Broward and Miami-Dade counties) by examining select population characteristics of the floodplain inhabitants. Dasymetric mapping is used to redistribute block group level census data to homogeneous inhabited zones of 30 m × 30 m. Because the 100 year floodplain does not correspond to block group boundaries, this data redistribution increases the resolution and accuracy of the floodplain population and their social characteristics. Data on poverty, age, vehicle ownership and mobile housing units are obtained for each 30 m × 30 m zone in the floodplain and is aggregated to the block group level. It is then used to assess evacuation assistance need (based on volume of need as well as concentration of need) for the floodplain in each block group. Results reveal variations in evacuation need across the floodplain. "Age" is the main driver of evacuation need along the coast. "Poverty" is a factor inland, in both urban and rural areas. "Lack of vehicle ownership" contributes to assistance need in coastal and inland urban areas, but not so much in rural areas. "Mobile housing" is a factor in rural areas. Miami-Dade County has higher volume and concentration of poor households lacking vehicular ownership. Palm Beach and Broward counties, on the other hand, have a more dominant presence of elderly and of mobile housing. These results have important implications for local and regional evacuation planning in the event of a 100 year flood. Highlights: Evacuation assistance need must be gauged by both volume and concentration of need. Hurricane evacuation plans should extend beyond surge zones to include inland areas. Evacuation plans must include remote rural areas due to high concentration of need. Targeted evacuation assistance is crucial due to different drivers of vulnerability.